2000
DOI: 10.1093/geront/40.5.612
|View full text |Cite
|
Sign up to set email alerts
|

"Outings to Your Taste": A Nutrition Program for the Elderly

Abstract: "Outings to Your Taste" is an innovative program that aims to improve the nutritional status and social network of elderly people who receive home-delivered meals. This article examines participation in one of the program's components, outings to community restaurants. Participation data were collected on-site and information about client characteristics was collected in at-home interview surveys of targeted clients (n = 144). While about half of the clients had tried at least one outing, more than 25% of them… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…During the interaction the robot would also make jokes and comment on a user's responses to promote the social dimensions of the interaction. We chose the restaurant finding activity as it has been found that going to restaurants can promote nutrition and social interactions while reducing isolation for the elderly (Richard, Gosselin, Trickey, Robitaille, & Payette, 2000). Furthermore, face-to-face interaction has been found to be the most preferable form of such a type of information retrieval for this population (Barrett, 2000).…”
Section: Restaurant Findermentioning
confidence: 99%
“…During the interaction the robot would also make jokes and comment on a user's responses to promote the social dimensions of the interaction. We chose the restaurant finding activity as it has been found that going to restaurants can promote nutrition and social interactions while reducing isolation for the elderly (Richard, Gosselin, Trickey, Robitaille, & Payette, 2000). Furthermore, face-to-face interaction has been found to be the most preferable form of such a type of information retrieval for this population (Barrett, 2000).…”
Section: Restaurant Findermentioning
confidence: 99%
“…In a quasi-experimental study, Roy and Payette (2006) established that meal delivery in Quebec increased energy intake by 120 kcal/d. The ''Outings to Your Taste'' program incorporated twice a month opportunities for Meals on Wheels clients to visit local restaurants with other clients and with the assistance of peer volunteers (Richard et al 2000). Process evaluation found a participation rate of 25% and those older adults who were socially isolated were more likely to take part (Richard et al 2000).…”
Section: Successful Programs For Promoting Food Intakementioning
confidence: 99%
“…The ''Outings to Your Taste'' program incorporated twice a month opportunities for Meals on Wheels clients to visit local restaurants with other clients and with the assistance of peer volunteers (Richard et al 2000). Process evaluation found a participation rate of 25% and those older adults who were socially isolated were more likely to take part (Richard et al 2000). Despite improving food intake, Canadian research has demonstrated that these programs do not resolve nutrition deficits; food intake remains insufficient to meet nutrient and energy requirements (Krondl et al 2003;Roy and Payette 2006).…”
Section: Successful Programs For Promoting Food Intakementioning
confidence: 99%
“…Nearly half of the studies (n=39) represent a cross-sectional single point in time (18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56). Thirty-two of these cross-sectional studies report on a single sample (18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46), and with the exception of one national sample (32), the samples were drawn from areas smaller than or equivalent to individual US states.…”
Section: Resultsmentioning
confidence: 99%
“…Six additional cross-sectional descriptive studies were identified (51, 52,53, 54, 55, 56). DiMaria-Ghalili compared client satisfaction surveys from MANNA meal recipients in Philadelphia to OAA recipients from the Northeast and nationally; she and her colleagues found that the MANNA recipients were more satisfied, but less food secure (51).…”
Section: Resultsmentioning
confidence: 99%